Is all high-risk behaviour premeditated? A qualitative exploratory approach to the self-regulation of habitual and risky driving behaviours. (October 2022) - Love, Steven; Truelove, Verity; Rowland, Bevan; Kannis-Dymand, Lee; Davey, Jeremy
Highlights: Speeding behaviours were commonly noted as habitual and unintentional. Phone use while driving was largely attributable to addiction and attitudes. The automaticity of the behaviours made them more difficult to modify. Driver mentality and social norms were perceived to inhibit behavioural change. Cognitive and behavioural strategies helped promote behavioural change. Abstract: The majority of research surrounding the intervention of risky driving behaviours has operated on the notion that offending behaviour is intentional, leading to a defined theoretical approach on deterrence. This study aimed to investigate the motivations, regulatory behaviours and resisting beliefs that contribute to the occurrence of risky driving behaviours, from the perspective that some behaviour may be unintentional and habitual by nature. An online sample of Australian drivers ( N  = 46) were recruited to complete a qualitative phone interview regarding their perceptions of risky driving behaviours. Thematic analysis revealed that firstly, speeding and the use of technology while driving (i.e., distraction) were the most commonly reported risky driving habits. Speeding in particular appeared to be both habitual and unintentional, whereas phone use while driving was attributable to addiction, impulses and attitudes. Factors such as drivers' mentality, the automaticity of the behaviour, and social norms were perceived to make habitual behaviours more difficult to change, whilst personal experiences with legal and physical consequences were perceived to increase risk perceptions and promote behavioural change. Participants also reported using cognitive reframing strategies and behaviours to increase and maintain awareness of the behaviours. Overall, this study has highlighted the resistant and multi-dimensional nature of risky driving habits, as well as the situational factors that preclude them. Based on the findings, future research may benefit by focusing efforts to understanding how habituality fits in the broader deterrence literature, and how such behaviours can be best intervened.